THE IMPLEMENTATION OF INDONESIAN GOVERNMENT POLICIES ON UNEMPLOYMENT MANAGEMENT - Piriyansa, M Agung; Rahmadanita, Annisa (Program Studi Studi Kependudukan dan Pencatatan Sipil, 2024)
The Identity Card (KTP) serves as an official population identification issued by the relevant authority and is valid throughout the Unitary State of the Republic of Indonesia. Despite this, in Semende Darat Ulu District, 9,520 out of 22,273 eligible individuals have yet to register for the E-KTP. This study aims to assess the implementation of the E-ID card service program in this district. Utilizing a qualitative research method with a descriptive approach, data were collected through interviews, observations, and documentation. The findings indicate that, in the communication dimension, the clarity of service implementation was satisfactory. Semende Darat Ulu Subdistrict effectively disseminated information about E-KTP recording times by notifying village officials and conducting school visits. The resource dimension, concerning both quantity and quality, was adequate for counter officers and E-KTP operators. The disposition dimension revealed that task distribution among employees was aligned with their competencies. The bureaucratic structure dimension showed that an SOP (Standard Operating Procedure) governs the E-KTP service process. However, challenges remain due to signal issues and adverse geographical conditions, such as frequent rain and power outages. Overall, three out of the four dimensions were found to be satisfactory, while one remains lacking. Therefore, the implementation of the E-KTP service program in Semende Darat Ulu District is categorized as good, though improvements are needed.